2018
DOI: 10.1021/acs.jpca.8b07119
|View full text |Cite
|
Sign up to set email alerts
|

The Hydropathy Scale as a Gauge of Hygroscopicity in Sub-Micron Sodium Chloride-Amino Acid Aerosols

Abstract: Sodium chloride, NaCl, is commonly used as a proxy for sea spray aerosols. However, field work has demonstrated that sea spray aerosols also often contain a significant organic component. In this work, we examine the effect of amino acids on the hygroscopic properties of NaCl aerosols using a Fourier transform infrared spectrometer coupled to a flowcell apparatus. It is found that the effect can be drastically different depending on the nature of the amino acid. More hydrophilic amino acids such as glycine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…3b) a continuous shrink in wet particle size was observed from 30 % to 80 % RH, and above 80 % RH the GFs increased slightly. Previous studies have reported that glycine particles started to absorb water above 60 % RH (Chan et al, 2005;Marsh et al, 2017;Darr et al, 2018) prior to deliquescence due to a capillary effect, which could be the potential reason for the shrinkage in their particle size in our study as a result of the microstructural rearrangement of particles upon humidification. The sizing of these structurally rearranged particles will be erroneous, especially at lower RH range, as the volume change of the particles upon wetting may be due not only to the water absorption but also the compaction of the original particles.…”
Section: Amino Acidsmentioning
confidence: 60%
“…3b) a continuous shrink in wet particle size was observed from 30 % to 80 % RH, and above 80 % RH the GFs increased slightly. Previous studies have reported that glycine particles started to absorb water above 60 % RH (Chan et al, 2005;Marsh et al, 2017;Darr et al, 2018) prior to deliquescence due to a capillary effect, which could be the potential reason for the shrinkage in their particle size in our study as a result of the microstructural rearrangement of particles upon humidification. The sizing of these structurally rearranged particles will be erroneous, especially at lower RH range, as the volume change of the particles upon wetting may be due not only to the water absorption but also the compaction of the original particles.…”
Section: Amino Acidsmentioning
confidence: 60%
“…Herein, restudies are conducted to make a good comparison between mixed and pure components using the IR technique. As can be seen from the glycine aerosols in Figure S1, spectra of wet and dry glycine are taken from the highest and the lowest RHs, and the feature bands were assigned with the help of literature , (shown in Table S1). Two representative peaks at 928 and 895 cm –1 attributed to ρ-CH 2 and ν-CC appeared at 85.6% RH, respectively, and then shifted to 915 and 893 cm –1 at 6.3% RH.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 In the amino acids, glycine is the smallest and simplest and has been found to be the most abundant in bioaerosols by Sun et al 18 with the identification in marine atmospheric aerosol samples. 19 A recent study observed dramatic effects of amino acids on the hygroscopic properties of inorganic aerosols, 20 leading to the modified CCN and physicochemical properties of atmospheric aerosols containing bioaerosols. 15,18,19,21,22 In our group's studies, the internally mixed glycine/NaNO 3 , glycine has been studied, and it was found that glycine promotes the crystallization of mixed droplets and inhibits the liquid−solid phase transition of inorganic salts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, composition of SSA vary with the seasons and biological activity (Parent et al, 2023). It has been shown to contain a significant organic component (Cavalli et al, 2004;Facchini et al, 2008), which has implications for its hygroscopicity and ice nucleation activity (Darr et al, 2018). Furthermore, SSA has been demonstrated to be geochemically important over geologic timeframes due to the presence of trace elements and metal pollution in aerosols derived from sea spray (Marx et al, 2014).…”
mentioning
confidence: 99%